2017
DOI: 10.18549/pharmpract.2017.01.873
|View full text |Cite
|
Sign up to set email alerts
|

Management of musculoskeletal pain in retail drug outlets within a Nigerian community: a descriptive study

Abstract: Objective:This work aimed to describe attitudes and practices of both community pharmacies and patent and proprietary medicine vendor (PPMV) outlets towards over-the-counter (OTC) analgesic use for musculoskeletal pain states within Zaria, Nigeria.Methods:The study was carried out in 2 phases from May to August 2016. Phase one was a cross-sectional survey of 40 retail drug outlets (10 community pharmacies and 30 PPMVs). A simulated patient scenario of a young adult male complaining of acute onset back pain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(36 reference statements)
1
8
0
3
Order By: Relevance
“…Community pharmacy professionals, being one of the most reachable healthcare professionals among the community, have great potential as a setting in primary health care services. This characteristic feature of community pharmacies provide a platform for more proactive contribution in self-care and managing a range of minor ailments [ 1 – 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacy professionals, being one of the most reachable healthcare professionals among the community, have great potential as a setting in primary health care services. This characteristic feature of community pharmacies provide a platform for more proactive contribution in self-care and managing a range of minor ailments [ 1 – 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study was that it was only designed to assess self-reported practice; the use of the simulated patient technique may be a more appropriate way to assess actual practice. Indeed, the use of simulated patients to assess analgesic recommendations have previously been reported in other contexts 42,43. Additionally, as this was a self-reported survey, response bias is possible.…”
Section: Discussionmentioning
confidence: 96%
“…Pada bagian akhir dari kasus diberikan sebuah pertanyaan "Apakah ada yang akan Anda rekomendasikan atau sarankan untuk ibu ini?". Kasus LBP pada penelitian ini merupakan kasus dari literatur terpublikasi [3,16] yang dimodifikasi berdasarkan diskusi dengan beberapa praktisi farmasi komunitas agar memperoleh gambaran yang riil dan sesuai dengan kondisi di masyarakat. Adapun modifikasi pada kasus LBP adalah sebagai berikut: 1) penambahan kalimat "tidak ada keluhan nyeri seperti rasa kesemutan, terbakar ataupun rasa seperti ditusuk jarum" untuk menegaskan tidak adanya gejala bahaya (alarm symptoms) yang membutuhkan rujukan ke dokter; 2) LBP yang semula disebabkan oleh berkebun diubah menjadi membersihkan rumah dan memindahkan barang berat untuk menyesuaikan penyebab dengan konteks Indonesia.…”
Section: Instrumen Penelitianunclassified